Oxylipin profile of human low-density lipoprotein is dependent on its extent of oxidation. (September 2019) - Surendran, Arun; Zhang, Hannah; Winter, Tanja; Edel, Andrea; Aukema, Harold; Ravandi, Amir
Abstract: Background and aims: Atherosclerosis is usually the underlying cause of heart attacks, strokes and peripheral vascular diseases – collectively known as cardiovascular diseases. Oxidation of low density lipoprotein (LDL) and its lipid content has an important role in the formation of lipid-laden atherosclerotic plaques. Not much is known about the impact of oxidative stress on bioactive oxylipin molecules present in LDL. The aim of this study is to understand the changes in oxylipin molecules present in LDL characterized by varying degrees of LDL oxidation. Methods: LDL was isolated from the pooled plasma of healthy normolipidemic volunteers and was subjected to in vitro copper-catalyzed oxidation for varying time intervals (0 h, 6 h, 12 h, 24 h and 30 h). At each time interval, oxylipins were isolated through solid phase extraction and quantified using a targeted LC/-MS/MS approach employing stable isotope dilution method. Results: Our results demonstrate that different forms of oxidized LDL (OxLDL) are characterized by specific oxylipin distribution and concentration. Compared to non-oxidized LDL, there is a significant increase in oxylipin generation ( p  ≤ 0.05) in OxLDL subjected to 12 h and 24 h of oxidation. Though linoleate derived oxylipins are the most abundant in OxLDL extracts, the concentration of particular oxylipin species differed with different degrees of oxidation. Specifically, two pro-inflammatory linoleate-derived triols, namely 9, 10, 13-triHOME and 9, 12, 13-triHOME, exhibited a concentration increase of ~25 fold in 12h-OxLDL compared to non-oxidized LDL. Moreover, Partial least squares Discriminant Analysis (PLS-DA) identified 10 oxylipins, primarily prostaglandins, which could serve as additional biomarkers for oxidative stress or cardiovascular risk assessment. Conclusions: Our data suggests that oxidative stress induces profound changes in the oxylipin content of LDL and the pattern of change is based on the extent of oxidation. Graphical abstract: Image 1 Highlights: Oxylipin profile of LDL changes dramatically during copper oxidation. Oxidation of LDL generates new oxylipins, with both pro- and anti-inflammatory properties. Oxylipin profile of LDL can determine the level of oxidation of the LDL particle.